Highly sensitive SERS immunosensor for the detection of amantadine in chicken based on flower-like gold nanoparticles and magnetic bead separation. (August 2018) - Ma, Mingfang; Sun, Jiefang; Chen, Yiqiang; Wen, Kai; Wang, Zhaopeng; Shen, Jianzhong; Zhang, Suxia; Ke, Yuebin; Wang, Zhanhui
Abstract: Here we report a novel ultrasensitive surface-enhanced Raman scattering (SERS) immunosensor based on the flower-like gold nanoparticles (AuNFs) and magnetic bead separation for homogeneous detection of amantadine (AMD) in chicken just by one-step. The 5, 5′-dithiobis (2-nitrobenzoicacid) (DTNB) modified AuNFs and N-(1-adamantyl) ethylenediamine (AEDA) conjugated denatured BSA (AEDA-dBSA) was used as the SERS nanoprobe. And the capture probe was anti-AMD monoclonal antibody (mAbs)-functionalized magnetic beads (MNBs-mAbs). An immunoreaction occurred between free AMD and SERS nanoprobe for competing limited binding sites of MNBs-mAbs. This work combined inherent sensitive property of SERS with antibody-antigen highly specificity recognition for the AMD detection. The analytical results showed that the SERS-based immunosensor was sensitive, simple and reliable with a limit of detection (LOD) of 0.005 ng/mL for AMD, which were 2 orders of magnitude better than an enzyme-linked immunosorbent assay based on the same immunoreagents. Analysis of AMD-spiked chicken samples revealed that the developed immunosensor provided accepted recoveries ranging from 74.76%-89.34% with coefficient of variation less than 15.04%. This strategy represents a simple, reliable, and universal approach for detection of chemical contaminants in food samples. Graphical abstract: Image 1 Highlights: A novel ultrasensitive SERS immunosensor was developed. Flower-like gold and magnetic bead are incorporated in immunosensor. The immunosensor was highly sensitive with a LOD of 0.005 ng/mL for AMD.